Implementation of the Authority of the Police Security Intelligence Unit Regarding Supervision of Explosives Abuse in Indonesia - Ristanto, Sandy Chesar; Hanim, Lathifah (UNISSULA Semarang, 2025)
Abstract. The misuse of explosives poses a significant threat to public security and order. Data indicates that cases of misuse are still frequently found in various regions of Indonesia. The Intelligence and Security Agency of the Indonesian National Police (Baintelkam Polri) recorded that from 2016 to 2020, the misuse of explosives occurred almost every year. Additionally, Operation Pekat Candi 2024, conducted by the Central Java Regional Police, uncovered 81 cases of explosive misuse, resulting in the arrest of 98 suspects and the seizure of 410 kilograms of explosives. This thesis aims to analyze the implementation of the authority of the Police Security Intelligence Unit in supervising the misuse of explosives in Indonesia and to examine the challenges and solutions affecting the implementation of this authority. This research employs an empirical juridical aproach with a descriptive-analytical specification. Primary data were obtained through interviews with representatives of the Intelligence and Security Unit of the Indonesian National Police Headquarters, while secondary data were collected from legislation, books, and academic journals. The research findings indicate that the implementation of the authority of the Police Security Intelligence Unit in overseeing the misuse of explosives in Indonesia is carried out through early detection, administrative and operational supervision, and intelligence measures to ensure compliance with aplicable regulations. The effectiveness of this supervision depends heavily on the availability of human resources, budget, infrastructure, and inter-agency coordination. Challenges in implementing this authority include internal constraints, such as a lack of personnel and technological suport, as well as external constraints, such as minimal public participation, weak inter-agency coordination, and inconsistencies in regional autonomy policies. The necessary solutions involve strengthening the legal structure through increased personnel capacity and the adoption of modern technology, updating legal substance to better adapt to evolving criminal methods, and enhancing legal culture through public education and socialization to encourage community involvement in explosives supervision.